If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 4 = -7 + 2x + 25 Reorder the terms: 4 + 4x = -7 + 2x + 25 Reorder the terms: 4 + 4x = -7 + 25 + 2x Combine like terms: -7 + 25 = 18 4 + 4x = 18 + 2x Solving 4 + 4x = 18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4 + 4x + -2x = 18 + 2x + -2x Combine like terms: 4x + -2x = 2x 4 + 2x = 18 + 2x + -2x Combine like terms: 2x + -2x = 0 4 + 2x = 18 + 0 4 + 2x = 18 Add '-4' to each side of the equation. 4 + -4 + 2x = 18 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 18 + -4 2x = 18 + -4 Combine like terms: 18 + -4 = 14 2x = 14 Divide each side by '2'. x = 7 Simplifying x = 7
| -7(-2-6b)+9b= | | 12p+3=30 | | pie=7.3m | | 2u-10=0 | | 2w+3.7=0.5 | | 13x-34=10x-10 | | (b-7)(b+3)=0 | | 2u-10=14 | | 800=16n^2+56n | | (x+20)+7=20 | | 3x+8+8y=15 | | 4d-3+2d=9 | | 2x+y=532 | | 1.25+-3= | | 17-s/4-10 | | 9+m=27+27 | | -6(x-2)-26=-14 | | 5*sin(x)+2=sin(x) | | 7n-54=2n+56 | | 5=2+3u | | (-3x+3y)(9x^2+9xy+9y^2)= | | 8+8w+(27+9w)=0 | | 20/25= | | 23x+23=34 | | 3(3x-1)-3(2x)=1 | | 3n+35= | | 0.9x-2.1-0.9=0.2(5-x) | | 0.029x+2=0.034x | | 7(y-6)+3y=10(y+1) | | 11+18=x+19 | | (2/9)g=8 | | 9(4x+1)=10(3x+2) |